Analysis of the Interlacing project: an articulation between scientific dissemination/diffusion and design - Arduino, Luiz Guilherme de Brito (2022)
It is understood that scientific knowledge needs to be accessed and understood by communities other than the scientific one and, for this, it requires an understanding of its language, because its presentation and appreciation are, most of the time, difficult to understand, leading to an involuntary elitization of knowledge. From a mapping of scientific dissemination/diffusion projects, it was identified that the Entrelaçar project (2021) of the Postgraduate Master’s Program in Applied Linguistics from the University of Taubaté-SP, by means of a series of e-books, promotes the diffusion of research from dissertations, with the intention of providing subsidies so that the mother and/or foreign language teacher can use them in the classroom. Thus, this research aims to analyze the Entrelaçar project by articulating it with Interaction Design. This is a methodological-qualitative research with a case study of the mentioned project. Items to be improved in the project were identified, such as the degree of interactivity between the user and the artifact. The e-book could include links and QR Codes that lead the user to other complementary digital content, such as videos, articles and even dissertations from which the material was originated.